Hemoglobin A1c Threshold for Reduction in Bone Turnover in Men With Type 2 Diabetes Mellitus - Joad, Sabaa; Ballato, Elliot; Deepika, FNU; Gregori, Giulia; Fleires-Gutierrez, Alcibiades Leonardo; Colleluori, Georgia; Aguirre, Lina; Chen, Rui; Russo, Vittoria; Fuenmayor Lopez, Virginia Carolina; Qualls, Clifford; Villareal, Dennis T.; et al. (Frontiers in Endocrinology, 2021)
ABSTRACT Background: Emerging data suggest that type 2 diabetes mellitus (T2D) is associated with increased risk for fractures despite relatively normal or increased bone mineral density (BMD). Although the mechanism for bone fragility in T2D patients is multifactorial, whether glycemic control is important in generating this impairment in bone metabolism remains unclear. The purpose of our study is to identify a hemoglobin A1c (A1c) threshold level by which reduction in bone turnover begins in men with T2D. Method: Cross-sectional analysis of baseline data from 217 men, age 35-65, regardless of the presence or absence of hypogonadism or T2D, who participated in 2 clinical trials. The following data were obtained: A1c by HPLC; testosterone and estradiol by LC/MS; bone turnover markers Osteocalcin[OC], C-terminal telopeptide [CTx] and sclerostin by ELISA; and BMD by DXA. Patients were grouped into 4 categories based of A1c (group I<6%,group II:6.1-6.4%, groupIII:6.5-6.9% and group IV ≥7 %). Threshold models were fit to data using nonlinear regression and group comparisons among the different A1c categories performed by ANOVA. Results: Threshold model and nonlinear regression showed an A1c cut-off of 7.0, among all choices of A1c’s, yields the least sum of squared errors. Comparison of bone turnover markers revealed relatively lower OC (p=0.002) and CTx (p=0.0002) in group IV (A1c≥7%), compared to the other groups. Analysis of men with T2D (n=94) showed relatively lower OC (p<0.001) and CTx (p<0.001) in those with A1c ≥7% compared to those <7%, respectively. The significance between the groups persisted even after adjusting for medications, p=0.003. Conclusion: Analysis across our entire study population showed a breakpoint A1c level of 7% or greater is associated with lower bone turnover. Also in men with T2D, an A1c ≥7% is associated with low bone turnover